PENELAAHAN KEBUTUHAN KOMPETENSI KEPALA SEKOLAH DALAM PENGELOLAAN ADMINISTRASI PENDIDIKAN ANAK USIA DINI - Andriani Chondro Retno; Sartini; Desilva Sindra Javanis; Sutama; Achmad Fathoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to evaluate the competency needs of school principals in managing the administration of early childhood education at Kindergarten Kemala Bhayangkari 67 Sragen. Early childhood education has an important role in shaping children's early development, and the role of school principals in ensuring effective educational administration is crucial. The research method used was descriptive analysis with a qualitative approach, where data was collected through in-depth interviews with school principals from various early childhood education institutions. The results of the analysis identified a number of key competencies needed by school principals, including leadership that is sensitive to children's needs, management of human, financial and material resources, strong communication skills, interpersonal skills, creativity and community involvement. Child-oriented leadership at Kemala Bhayangkari Kindergarten 67 Sragen emphasizes the interests and needs of children as the main priority, with a focus on the optimal growth and development of each child. Leaders at this institution understand the characteristics and developmental needs of early childhood, encourage an exploratory learning approach, focus on developing social and emotional skills, and ensure parent and community involvement. Through this approach, Kindergarten Kemala Bhayangkari 67 Sragen ensures the best educational experience for children, forms a strong foundation for further development, and helps them grow into talented individuals who contribute positively to society.